The mainstream cosmetics industry in Malaysia and the emergence, growth, and prospects of halal cosmetics - Swidi, Abdullah; Cheng, Wie; Hassan, Mohamad Ghozali; Al-Hosam, Asma; Mohd Kassim, Abdul Wahid (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
Muslims all over the world are almost totally dependent on cosmetics products made by non-Muslims. Moreover, Muslims seem to have taken the back seat when it comes to the cosmetics industry which is dominated, and to a certain degree monopolized, by non-Muslims. Thus, the issue of Halal ingredients in cosmetics products poses serious challenges. On the other hand, the growing consumer awareness and hence demand for Halal products, not just Halal food and drink, has provoked existing and new players in the cosmetics industry to make Halal products. However, in the global cosmetics industry there is a new trend that is the wave of Halal cosmetics and personal care products. The increasing number of Muslims around the world and the raise of awareness among their recent generations are two crucial reasons behind the new trend in the change of behaviors among Muslim consumers. The faith-based new wave in the global cosmetics market may be reflected in the recent change in the global scenario. Since the Muslim consumers constitute nearly 20% of the population of the world, they started pushing the mainstream cosmetics industry to listen to their voice and satisfy their needs in offering Shariah-compliant products.